2021
DOI: 10.3389/fcimb.2021.646348
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis and Implication of the Gut Microbiota in Diabetic Retinopathy

Abstract: The pathogenesis of type 2 diabetes mellitus (T2DM) is commonly associated with altered gut bacteria. However, whether the microbial dysbiosis that exists in human diabetic patients with or without retinopathy is different remains largely unknown. Here, we collected clinical information and fecal samples from 75 participants, including 25 diabetic patients without retinopathy (DM), 25 diabetic patients with retinopathy (DR), and 25 healthy controls (HC). The gut microbial composition in the three groups was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 52 publications
10
120
2
Order By: Relevance
“…Recent studies demonstrated the alterations and possible application prospects of the gut microbiome in patients with other ocular neovascular diseases, such as DR (Das et al, 2021;Huang et al, 2021) and retinopathy of prematurity (Skondra et al, 2020). Das et al (2021) recognized a reduction in anti-inflammatory, probiotic and other bacteria that could be pathogenic in the microbiomes of patients with both diabetes mellitus and DR, compared to the healthy controls, and the changes observed in DR patients were more pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies demonstrated the alterations and possible application prospects of the gut microbiome in patients with other ocular neovascular diseases, such as DR (Das et al, 2021;Huang et al, 2021) and retinopathy of prematurity (Skondra et al, 2020). Das et al (2021) recognized a reduction in anti-inflammatory, probiotic and other bacteria that could be pathogenic in the microbiomes of patients with both diabetes mellitus and DR, compared to the healthy controls, and the changes observed in DR patients were more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Das et al (2021) recognized a reduction in anti-inflammatory, probiotic and other bacteria that could be pathogenic in the microbiomes of patients with both diabetes mellitus and DR, compared to the healthy controls, and the changes observed in DR patients were more pronounced. Huang et al (2021) indicated the potential use of gut microbiota as a biomarker of DR, which could be helpful for diagnosis in clinical applications. Moreover, it has been suggested that the effect of antihyperglycemic drugs might be involved in the connection between the gut microbiota and DR, and targeting the gut microbiome could be novel therapeutic strategies in treating DR (Rowan and Taylor, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS derived from Bacteroidetes and Desulfobacterota could generate inflammatory injuries, trigger abnormal equilibrium of metabolism, and inhibit endotoxin tolerance, all of which are related to the pathogenesis of retinopathy. 18 , 60 Influence of endotoxin-mediated retinal inflammation on phenotype of diabetic retinopathy. Additionally, Vagaja et al revealed that endotoxin-mediated retinal inflammation may have impact on phenotype of DR, that is, the systemic LPS exposure in Ins2 Akita mice could accelerate the damage of retinal capillary endothelium and attenuation of the retina.…”
Section: Hypothesis That Gut Microbiota Cause Drmentioning
confidence: 99%
“… 16 , 17 However, little has been understood regarding the molecular mechanisms of intestinal dysbiosis and how they induce retinopathy in patients with DM. Recently, data indicate that changes in the gut microbiome act as a key internal environmental modulator which favorably affects the pathogenetic processes underlying the micro-complications of DM such as DR. 18 …”
Section: Introductionmentioning
confidence: 99%